REMOVAL OF SEPARATED INSTRUMENTS WITH MASSERANN TECHNIQUES: TWO CASE REPORTS - Hakan Göktürk; İsmail Özkoçak (Cumhuriyet University, 2017)
Instrument fracture is a procedural mishap that prevents efficient cleaning and shaping of the root canal. When bypassing the fracture fails, the fragment must be removed. Many techniques and devices have been described to remove fragments from the root canal. The Masserann Kit is a widely used instrument for the removal of fragments. These clinical cases describe use of the Masserann Kit to remove separated instruments blocking the entire canal in posterior teeth.